Belarus the last European dictatorship - Wilson, Andrew, 1961- (New Haven London Yale University Press, 2021)
A comprehensive and revelatory history of modern Belarus - from independence to 2020's contested election In 2020 Belarus made headlines around the world when protests erupted in the aftermath of a fraught presidential election. Andrew Wilson explores both Belarus's complicated road to nationhood and its politics and economics since it gained independence in 1991. Two new chapters reveal the extent of Aliaksandr Lukashenka's grip on power, the growth of the opposition movement and the violent crackdown that followed the vote. Wilson also examines the prospects for Europe as a whole of either Lukashenka's downfall or his survival with Russian support. "Andrew Wilson has done all students of European politics a great service by making the history of Belarus comprehensible and by showing how the future of Belarus might be different than its present."--Timothy Snyder, author of Bloodlands: Europe Between Hitler and Stalin
pt. I A Belarus: A History of Crossroads -- 1. Polatsk -- 2. Litva -- 3. Ruthenia -- 4. Uniate-land -- 5. Belarus Begins -- 6. Belarus Begins Again: The Traumatic Twentieth Century -- pt.II Independent Belarus -- 7. The Building Blocks of National Identity -- 8. Politics Either Side of Independence, 1989 -- 1994 -- 9. Building Authoritarianism: Lukashenka's First Term -- 10. Building an Authoritarian State: Lukashenka's Second Term -- 11. The Third Term: The Edifice Crumbles -- 12. The Myth of the Belarusian Economic Miracle
Includes bibliographical references and index
"This new edition published in paperback in 2021"
Print version record
JSTOR
Keywords: Lukashenko, Aleksandr, -- 1954-; Lukashenko, Aleksandr, -- 1954-; Belarus -- History; Belarus -- Politics and government; Political culture -- Belarus -- History; Belarus -- Politics and government -- 1991-; Dictatorship -- Europe -- Case studies; Biélorussie -- Histoire; Biélorussie -- Politique et gouvernement; Biélorussie -- Politique et gouvernement -- 1991-; Dictature -- Europe -- Études de cas; HISTORY -- Europe -- Eastern; Dictatorship; Political culture; Politics and government; Belarus; Europe; Since 1991; Case studies; History